The Influence Of Using Manipulative Media To Learning Outcomes To Mathematics Of Grade VB Elementary School Student In Banjar Kertahayu Way Pengubuan District - Vira Fahrena Agiyusera; Rahayu Soraya; Qomario Qomario; Agus Riyanto (Perkumpulan Dosen Muda (PDM) Bengkulu, 2022)
This study aims to determine the effect of the use of manipulative media on the mathematics learning outcomes of class VB students at SD Negeri 3 Banjar Kertahayu, Way Pengubuan District. The problem in this research is the low mathematics learning outcomes of class VB SD Negeri 3 Banjar Kertahayu, Way Pengubuan District. The method used in this research is quantitative with the type of pre-experimental research one group pretest-posttest design which is used to determine the effect of a treatment on research subjects. The data of this study were obtained from the pretest and post-test scores, with the instrument in the form of multiple-choice questions of as many as 15 questions. The results of hypothesis testing obtained t count t table that is 6.482 2.056 with a Significant level of 0.000 0.05, then Ha is accepted and Ho is rejected. This means that there is a significant effect of using manipulative media on the mathematics learning outcomes of class VB students at SD Negeri 3 Banjar Kertahayu, Way Pengubuan District.